Space Weather, Environment and Societies - Lilensten, Jean.; Bornarel, Jean.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Our planet exists within a space environment affected by constantly changing solar atmosphere producing cosmic particles and electromagnetic waves. This "space weather" profoundly influences the performance of our technology because we primarily use two means for transmitting information and energy; namely, electromagnetic waves and electricity. On an everyday basis, we have developed methods to cope with the normal conditions. However, the sun remains a fiery star whose 'angry' outbursts can potentially destroy spacecrafts, kill astronauts, melt electricity transformers, stop trains, and generally wreak havoc with human activities. Space Weather is the developing field within astronomy that aims at predicting the sun$1 (Bs violent activity and minimizing the impacts on our daily lives. Space Weather, Environment, and Societies explains why our technological societies are so dependent on solar activity and how the Sun disturbs the transmission of information and energy. Footnotes expand specific points and the appendices facilitate a more thorough command of the physics involved. This beautifully illustrated book is written for astronomy and nature enthusiasts as well as for the undergraduate/graduate level readers who would like to better master the physics of near space.s
Introduction. Acknowledgements -- The sun -- The formation of the stars and the sun -- The characteristics of the sun -- A representation of the sun -- The internal structure of the sun -- The photosphere, solar radiation, the solar wind -- The thermal profile of the solar atmosphere -- Solar dynamics -- The sun: at the source of space weather -- The earth -- The earth within the solar system -- The internal structure of the earth: the geomagnetic field -- The atmosphere of the earth -- The magnetosphere -- Toward a space weather -- The consequences of solar agressions on our technological environment -- Other impacts of solar activity -- Space weather in order to forecast -- Appendices -- A few useful constants -- References. Word glossary. Glossary of names. Acronyms and logos. Index.
Keywords: Physics; Atmospheric sciences; Astronomy; Astrophysics; Cosmology; Engineering; Environmental sciences; Physics; Astronomy, Astrophysics and Cosmology; Environmental Physics; Atmospheric Sciences; Engineering, general; Electronic books